Optimal age of surgery for children with thyroglossal duct cysts: A single-institution retrospective study of 340 patients - Wang, Yingli; Yang, Gang (Frontiers in Pediatrics, 2023)
Objective: The recommended age of surgery for thyroglossal duct cysts (TGDC) in children is inconclusive. This study aimed to explore the optimal age of surgery by analyzing the natural history of the disease and the association between the age of surgery and postoperative complications. Methods: All TGDC patients who underwent a modified Sistrunk procedure at our hospital between March 2010 and May 2022 were reviewed retrospectively. The evaluation was focused on the age of preoperative symptomatic cystic infection, pathological inflammation, postoperative wound infection and recurrence. Results: Of the 340 patients included in the study, the median age of surgery was 47.5 months (IQR, 24.1-61.6). Preoperative symptomatic cystic infection and pathological inflammation frequency were 27.1% (n=92) and 48.5% (n=165). The cumulative hazard of symptomatic cystic infection and pathological inflammation increased steadily with age. The age of 50% cumulative incidence of symptomatic cystic infection and pathological inflammation was 97 months and 71 months, respectively. Postoperative wound infection was higher in patients with younger age (OR = 0.96, 95%CI 0.93~0.98, P<0.001) and symptomatic cystic infection (OR = 8.16, 95%CI 2.54~36.86, P = 0.002). There was no significant association between the age of surgery and recurrence. Conclusion: Though wound infection was weakly associated with younger age, the symptomatic cystic infection increasing with age has a more remarkable impact on wound infection after the Sistrunk procedure. The recurrence rate did not increase in young patients receiving surgery. Therefore, the Sistrunk procedure was safe and effective at a young age, and prompt operation in children with TGDC once diagnosed was reasonable.